Mechanical properties of concrete containing untreated palm oil fuel ash and egg shell powder - Abdul Ghaffar, Fatin Shafirah; Mohd Zuki, S. S.; Shahidan, S.; Mohamed Nazri, Fadzli; Abdul Rahim, Mustaqqim; Mohammad Azmi, Mohamad Azim; Abdul Rahman, Norashidah; W. Ibrahim, M. H. (Springer, 2021)
This study aims to use two (2) waste products, namely Palm Oil Fuel Ash (POFA) and Egg Shell Powder (ESP) as cement replacement in concrete. This is because the properties of POFA and ESP are similar to the properties of cement. The objective of this study is to determine the mechanical properties (compressive strength and tensile strength) of concrete containing POFA and ESP as cement replacement. With both properties known, the optimum percentage of POFA and ESP as cement replacement can then be determined. The percentage of replacement of POFA was fixed at 20%, however the percentages of ESP varied from 0 to 20%. Six 100 100 100 mm cubes and six 100 200 mm cylinders were prepared for each variation of percentages. The cubes and cylinders were tested for compressive and tensile strength after 7 and 28 days of water curing. Generally, as the percentages of ESP increased, the workability, compressive strength and tensile strength of the concrete sample decreased. In conclusion, the combination of POFA and ESP as cement replacement in concrete is only able to achieved 76% of targeted strength.